The iron raven - Kagawa, Julie (Kagawa, Julie. Iron fey: evenfall, 2021)
A first entry in a standalone trilogy set in the world of The Iron Fey finds King Oberon's right-hand jester, Puck, sharing his story while teaming up with Iron Queen Meghan Chase, prince consort Ash and allies old and new to confront a threat to the lands of Faery.